Kompetensi Andragogik Tutor dalam Melaksanakan Pembelajaran Pendidikan Kesetaraan Paket C - Rahmayanti, Aulia; Wisroni, Wisroni (Penerbit Aksara Rentaka Siar (ARS), 2019)
This research was motivated by the success of the Paket C education program in SPNF-SKB Region I Padang city, it seen from the satisfying learning citizen test scores. The researcher suspected that the cause of the success of the Paket C program was because of the tutor’s andragogic competence. The purpose of this research is to describe the tutor’s andragogic competencies which are seen from the ability to motivate the learning population, explain the learning objectives, present the material with relevant methods, use tools, and learning media, create a conducive learning climate and respond to each respondent's learning. This type of research is quantitative descriptive research. The population in this research were 50 peoples who studied the package C program. Samples were taken in 80% of the population that numbered 30 peoples using cluster random sampling method. The technique of collecting data uses a questionnaire. While the data collection tool uses a list of statements (questionnaires). The data analysis technique uses the percentage formula. The results showed that the tutor’s andragogic competence in implementation of learning in package C education which included abilities in: (1) motivating learning citizens were categorized very good, (2) explaining learning objectives were categorized good, (3) presenting material with relevant methods categorized very good, (4) using tools and learning media categorized good, (5) creating a conducive learning climate that is categorized very good and (6) responding to each respondent's learning is categorized very good.